12x - 28 = 7x - 63
Subtract 7x from each side:
5x - 28 = -63
Add 28 to each side:
5x = -35
Divide each side by 5:
x = -7
2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9
9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)
-46 = 3x + 7x
13x
x=6
The required equation is: -7x = 63
2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9
7x + 5 = 68 subtract 5 from both sides 7x = 63 divide both sides by 7 x = 9
9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)
-46 = 3x + 7x
7x + y = 8 Subtract 7x from each side of the equation: y = -7x + 8
13x
x=6
It is 9x
-7x + 5 = -9 -7x = -14 7x = 14 x = 2
7x + y = 4y = 4 - 7x
7x is still the slope, no matter what x equals.